Point‐of‐care N‐terminal pro B‐type natriuretic peptide assay to screen apparently healthy cats for cardiac disease in general practice - Ta‐Li Lu; Etienne Côté; Yu‐Wen Kuo; Hao‐Han Wu; Wen‐Yen Wang; Yong‐Wei Hung (Journal of Veterinary Internal Medicine, 2021)
Abstract Background Point‐of‐care (POC) N‐terminal pro B‐type natriuretic peptide (NT‐proBNP) ELISA test has been evaluated for screening cats for cardiac disease in the referral veterinary setting but less is known about its use in general practice (GP). Objectives To evaluate the diagnostic utility of a POC NT‐proBNP ELISA in cats seen in GPs. Animals Two hundred and seventeen apparently healthy cats from 21 GPs. Methods This was a prospective, cross‐sectional study. Cardiac auscultation and POC NT‐proBNP ELISA were done by veterinarians at their GPs. After enrollment at GPs, cats were sent to a cardiology referral hospital for cardiac auscultation and echocardiographic diagnosis. Results were interpreted based on whether cats had normal or abnormal echocardiographic findings. Results Point‐of‐care NT‐proBNP ELISA results differentiated cats in the abnormal group from those in the normal group with a sensitivity of 43%, specificity of 96%. In cats with a heart murmur at GPs, POC NT‐proBNP ELISA results differentiated cats in the abnormal group from those in the normal group with a sensitivity of 71% and a specificity of 92%. Conclusion and Clinical Importance In apparently healthy cats in GPs, positive POC NT‐proBNP results are associated with heart disease, warranting an echocardiogram, but negative results do not reliably exclude heart disease. These results suggest POC NT‐proBNP is not an effective screening test for apparently healthy cats in GPs, although its performance is improved if it is used only in cats that have a heart murmur.